2020
DOI: 10.3390/biom10030465
|View full text |Cite
|
Sign up to set email alerts
|

2,3,4′,5-Tetrahydroxystilbene-2-O-β-D-Glucoside (THSG) Activates the Nrf2 Antioxidant Pathway and Attenuates Oxidative Stress-Induced Cell Death in Mouse Cochlear UB/OC-2 Cells

Abstract: Oxidative stress plays a critical role in the pathogenesis of hearing loss, and 2,3,4 ,5-tetrahydroxystilbene-2-O-β-D-glucoside (THSG) exerts antioxidant effects by inhibiting reactive oxygen species (ROS) generation. With the aim of developing new therapeutic strategies for oxidative stress, this study investigated the protective mechanism of THSG in vitro using a normal mouse cochlear cell line (UB/OC-2). The THSG and ascorbic acid have similar free radical scavenger capacities. H 2 O 2 , but not THSG, reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 33 publications
2
12
0
Order By: Relevance
“…It has also been shown that THSG inhibits glutamate-induced neurotoxicity via suppression of ROS production [43]. Our previous study reported that THSG has free radical scavengers and activates the Nrf2 signaling pathway to mitigate H 2 O 2 -induced ototoxicity [31]. Here, this study demonstrated that THSG suppressed gentamicin-induced ototoxicity by inhibiting ROS production and activating the antioxidant enzyme, SOD (Figure 2).…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…It has also been shown that THSG inhibits glutamate-induced neurotoxicity via suppression of ROS production [43]. Our previous study reported that THSG has free radical scavengers and activates the Nrf2 signaling pathway to mitigate H 2 O 2 -induced ototoxicity [31]. Here, this study demonstrated that THSG suppressed gentamicin-induced ototoxicity by inhibiting ROS production and activating the antioxidant enzyme, SOD (Figure 2).…”
Section: Discussionsupporting
confidence: 62%
“…In our previous report, no effect on the survival of UB/OC-2 cells treated with THSG at different concentrations (5–40 μM) for 48 h was seen [ 31 ]. To further investigate whether THSG protects gentamicin-treated UB/OC-2 cells from oxidative stress, the levels of ROS were measured by flow cytometry using the indicator dye 2′,7′-dichlorofluorescein diacetate (DCFDA).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Decreasing the expression of Beclin-1 and LC3-II in autophagy pathways AD-like APP transgenic mice 120, 240 μM/kg Antagonizing the effects of amyloid plaques or inhibiting the formation of amyloid plaques directly reducing the cell damage caused by ROS and electrophilic substances, which maintains the physiological balance of oxidation-antioxidation in the body (Stępkowski and Kruszewski, 2011;Bellezza et al, 2018). In H 2 O 2 -induced oxidative stress of UB/OC-2 cells, TSG (5, 10, 20, 40 μM) showed a strong ability of antioxidant stress by increasing the level of antioxidant/detoxification enzymes such as heme oxygenase 1 (HO-1), NQO1, glutathione-s-transferase (GST), and UGT, as well as inhibiting the excessive production of ROS, apoptosis, and autophagy, which was attributed to the activation of the Nrf2 pathway (Wu et al, 2020). These results suggest that TSG-mediated activation of the Nrf2 signaling pathway may be an important mechanism of enhancing endogenous antioxidant defense system.…”
Section: Molecular Mechanisms Referencesmentioning
confidence: 99%
“…Moldenke ( He et al, 2015 ). Numerous studies have found that THSG exerts antioxidant effects by protecting cells from oxidative damage caused by H 2 O 2 through increasing SOD activity, reducing MDA content, and inhibiting ROS production ( Yang et al, 2014 ; Wu et al, 2020 ). In hairless skin model, the extract of Reynoutria multiflora could up regulate SOD in a dose-dependent manner, thereby reducing UVB-induced oxidative damage, suggesting that the extract of Reynoutria multiflora contains anti skin photoaging agent ( Hwang et al, 2006 ).…”
Section: Glycosidesmentioning
confidence: 99%